2004
DOI: 10.1016/j.na.2004.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Special standard static space–times

Abstract: Essentially, some conditions for the Riemannian factor and the warping function of a standard static space-time are obtained in order to guarantee that no nontrivial warping function on the Riemannian factor can make the standard static space-time Einstein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In [34, p. 228-230] and [16, p. 38-39] the authors proved that if (F, g F ) is compact and f ≡ 0 is a solution of (3.10), then the scalar curvature τ g F is constant (see [24] also). So, by (3.12) and the well known results about the spectrum of the Laplace-Beltrami operator on a compact Riemannian manifold without boundary (see [13]), there results: On the other hand, in [24, Proposition 2.7] the author proved that (see also [26]):…”
Section: Energy Conditions and Implicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…In [34, p. 228-230] and [16, p. 38-39] the authors proved that if (F, g F ) is compact and f ≡ 0 is a solution of (3.10), then the scalar curvature τ g F is constant (see [24] also). So, by (3.12) and the well known results about the spectrum of the Laplace-Beltrami operator on a compact Riemannian manifold without boundary (see [13]), there results: On the other hand, in [24, Proposition 2.7] the author proved that (see also [26]):…”
Section: Energy Conditions and Implicationsmentioning
confidence: 97%
“…The following formula of the curvature Ricci tensor can be easily obtained from [11,26,27,69]. Proposition 2.3.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, putting Y = W and Y = ∇f in (22) and using the fundamental equation, respectively we obtain Ric(W, W ) = Ric(∇f, W ) = 0.…”
Section: Isotropic Casementioning
confidence: 99%
“…As a consequence, it is shown that if the complete Riemannian factor manifold F satisfies the nonreturning property and has a pseudoconvex geodesic system and if the warping function f : F → (0, ∞) is bounded from above then the standard static space-time (a, b) f × F is geodesically connected. In [13], some conditions for the Riemannian factor and the warping function of a standard static space-time are obtained in order to guarantee that no nontrivial warping function on the Riemannian factor can make the standard static space-time Einstein. In a recent note [29], the authors discussed conditions for static Killing vector fields to be standard and then they obtained an interesting uniqueness result when the so called natural space (in the case of a standard static space-time, this is the Riemannian part) is compact.…”
Section: Introductionmentioning
confidence: 99%